Prognostic utility of estimated albumin excretion rate in chronic kidney disease: results from the Study of Heart and Renal Protection. Issue 2 (14th January 2017) - Mafham, Marion M; Staplin, Natalie; Emberson, Jonathan; Haynes, Richard; Herrington, William; Reith, Christina; Wanner, Christoph; Walker, Robert; Cass, Alan; Levin, Adeera; Fellström, Bengt; Jiang, Lixin; et al.
Abstract: Background: Estimated albumin excretion rate (eAER) provides a better estimate of 24-h albuminuria than albumin:creatinine ratio (ACR). However, whether eAER is superior to ACR in predicting end-stage renal disease (ESRD), vascular events (VEs) or death is uncertain. Methods: The prognostic utility of ACR and eAER (estimated from ACR, sex, age and race) to predict mortality, ESRD and VEs was compared using Cox proportional hazards regression among 5552 participants with chronic kidney disease in the Study of Heart and Renal Protection, who were not on dialysis at baseline. Results: During a median follow-up of 4.8 years, 1959 participants developed ESRD, 1204 had a VE and 1130 died (641 from a non-vascular, 369 from a vascular and 120 from an unknown cause). After adjustment for age, sex and eGFR, both ACR and eAER were strongly and similarly associated with ESRD risk. The average relative risk (RR) per 10-fold higher level was 2.70 (95% confidence interval 2.45–2.98) for ACR and 2.67 (2.43–2.94) for eAER. Neither ACR nor eAER provided any additional prognostic information for ESRD risk over and above the other. For VEs, there were modest positive associations between both ACR and eAER and risk [adjusted RR per 10-fold higher level 1.37 (1.22–1.53) for ACR and 1.36 (1.22–1.52) for eAER]. Again, neither measure added prognostic information over and above the other. Similar results were observed when ACR and eAER were related to vascular mortality [RR per 10-fold higher level: 1.64 (1.33–2.03) and 1.62 (1.32–2.00), respectively] or to non-vascular mortality [1.53 (1.31–1.79) and 1.50 (1.29–1.76), respectively]. Conclusions: In this study, eAER did not improve risk prediction of ESRD, VEs or mortality.